2022
DOI: 10.3390/v14071415
|View full text |Cite
|
Sign up to set email alerts
|

Potential Autoimmunity Resulting from Molecular Mimicry between SARS-CoV-2 Spike and Human Proteins

Abstract: Molecular mimicry between viral antigens and host proteins can produce cross-reacting antibodies leading to autoimmunity. The coronavirus SARS-CoV-2 causes COVID-19, a disease curiously resulting in varied symptoms and outcomes, ranging from asymptomatic to fatal. Autoimmunity due to cross-reacting antibodies resulting from molecular mimicry between viral antigens and host proteins may provide an explanation. Thus, we computationally investigated molecular mimicry between SARS-CoV-2 Spike and known epitopes. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 83 publications
1
34
0
Order By: Relevance
“…Particular attention has been paid to the spike protein of SARS‐CoV‐2 as it serves as a major antigen. As shown using the bioinformatic approaches, its motifs revealed molecular mimicry with various components of the cardiovascular system (e.g., cGMP‐dependent protein kinase 1, ephrin‐B2, thrombopoietin, and tropomyosin), immune system (e.g., tumor necrosis factor receptors, interleukin‐6 receptor), and nervous system (phosphacan, attractin, and teneurin‐4) 26–28 . However, the potential for such mimicry is much higher since, in addition to spike protein, the genome of SARS‐CoV‐2 encodes 3 other structural proteins, 16 nonstructural proteins (NSP), and 9 accessory proteins 29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particular attention has been paid to the spike protein of SARS‐CoV‐2 as it serves as a major antigen. As shown using the bioinformatic approaches, its motifs revealed molecular mimicry with various components of the cardiovascular system (e.g., cGMP‐dependent protein kinase 1, ephrin‐B2, thrombopoietin, and tropomyosin), immune system (e.g., tumor necrosis factor receptors, interleukin‐6 receptor), and nervous system (phosphacan, attractin, and teneurin‐4) 26–28 . However, the potential for such mimicry is much higher since, in addition to spike protein, the genome of SARS‐CoV‐2 encodes 3 other structural proteins, 16 nonstructural proteins (NSP), and 9 accessory proteins 29 .…”
Section: Introductionmentioning
confidence: 99%
“…As shown using the bioinformatic approaches, its motifs revealed molecular mimicry with various components of the cardiovascular system (e.g., cGMPdependent protein kinase 1, ephrin-B2, thrombopoietin, and tropomyosin), immune system (e.g., tumor necrosis factor receptors, interleukin-6 receptor), and nervous system (phosphacan, attractin, and teneurin-4). [26][27][28] However, the potential for such mimicry is much higher since, in addition to spike protein, the genome of SARS-CoV-2 encodes 3 other structural proteins, 16 nonstructural proteins (NSP), and 9 accessory proteins. 29 For example, one study found the homology between the viral open reading frames 1a and 1b, and between the multi-domain NSP3, and the human proteins: mono-ADP-ribosyltransferase, mono-ADP-ribosyl-transferase, and ADPribose glycohydrolase as well as between open reading frame 7b and the low-density lipoprotein receptor-related protein 2.…”
mentioning
confidence: 99%
“…Kanduc and Shoenfeld 25 conducted a quantitative peptide sharing analysis, which demonstrated massive heptapeptide sharing between the SARS‐CoV‐2 SP and human proteins. The significant overlap between the SARS‐CoV‐2 SP and human proteins may be the connection that creates a mutual pathway between COVID‐19 infection, vaccination, and postinfection/vaccination autoimmune responses 26 …”
Section: Discussionmentioning
confidence: 99%
“…Hence, based on the current compendium of SARS-CoV-2-reactive TCRs (Bagaev et al, 2020), which may not be comprehensive, there was no evidence for viral persistence at the site of disease in our cohort. A more plausible hypothesis, given reports of cross-reactivity between SARS-CoV-2 and human antigens (Nunez-Castilla et al, 2022; Vojdani and Kharrazian, 2020), is that the PCLD TCR repertoire is directed against as yet unknown respiratory autoantigens. Identifying the antigenic targets of the PCLD T cell repertoire may present opportunities for more specific therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%